O papel de um gestor do desporto no futebol de formação - Hugo José Rodrigues Gomes (2024)
This report was prepared with the aim of obtaining a master's degree in Sports Management from the Faculty of Sport of the University of Porto. It aims to report on the internship that was carried out at Sport Comércio e Salgueiros, in the youth football department, lasting eight and a half months, between September 2023 and May 2024. The relevance of this internship lies in my conviction that a club can only be well run with the support of well-qualified professionals in this area and, in this sense, the club that has hosted me has made a significant contribution to my professional and personal development. Sport Comércio e Salgueiros, founded in Porto in 1911, has a history characterised by difficulties and failures, but also by several achievements. It currently has a significant number of athletes, which shows the importance of this club in training young talents for Portuguese football and its influence on the local community. In this report, I also refer to the various tasks I carried out during this internship period, which gave me a practical insight into the day-to-day operations of a football club and allowed me to develop personal skills that are essential for my professional life in sports management.